2022
DOI: 10.7759/cureus.31342
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effect on Health-Related Quality of Life in Patients With COVID-19 Requiring Hospitalization Compared to Non-hospitalized COVID-19 Patients and Healthy Controls

Abstract: BackgroundIn this study, we aimed to evaluate the health-related quality of life (HRQL) in patients with severe coronavirus disease 2019 (COVID-19) six months after their hospitalization and compare it to that of nonhospitalized patients with mild COVID-19 and healthy controls. MethodologyParticipants were enrolled between September 2021 and April 2022 and included hospitalized COVID-19 patients at General Hospital of Athens "Hippocration" who had been discharged at least six months prior to enrollment, non-ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Our study also revealed that deterioration in QoL at work was predicted by younger age, both during and after acute phase of the SARS‐CoV‐2 infection. Our results resembled the observation from a small cohort assessed with four different questionnaires before and 6 months after hospitalization due to COVID‐19 that revealed a decrease in QoL, especially in younger individuals, that was, between 41 and 60 years 24 . On the other hand, an online questionnaire survey of 385 Indonesian patients showed that the risk of persistent post‐COVID fatigue, affecting QoL in the aspect of pain and anxiety or depression, was increased in older people and those previously hospitalized 25 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our study also revealed that deterioration in QoL at work was predicted by younger age, both during and after acute phase of the SARS‐CoV‐2 infection. Our results resembled the observation from a small cohort assessed with four different questionnaires before and 6 months after hospitalization due to COVID‐19 that revealed a decrease in QoL, especially in younger individuals, that was, between 41 and 60 years 24 . On the other hand, an online questionnaire survey of 385 Indonesian patients showed that the risk of persistent post‐COVID fatigue, affecting QoL in the aspect of pain and anxiety or depression, was increased in older people and those previously hospitalized 25 .…”
Section: Discussionsupporting
confidence: 89%
“…Our results resembled the observation from a small cohort assessed with four different questionnaires before and 6 months after hospitalization due to COVID-19 that revealed a decrease in QoL, especially in younger individuals, that was, between 41 and 60 years. 24 On the other hand, an online questionnaire survey of 385 Indonesian patients showed that the risk of persistent post-COVID fatigue, affecting QoL in the aspect of pain and anxiety or depression, was increased in older people and those previously hospitalized. 25 Thus, as it has been shown in a recent meta-analysis, both in younger and older COVID-19 survivors, symptoms of the CFS, such as fatigue, headache, and myalgia, are highly prevalent, and possibly associated with a poorer QoL.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have tried to identify what factors influence longterm quality of life outcomes in COVID-19. Female sex is the most frequently described determinant, in keeping with our findings (11,12,(17)(18)(19)(20)(21)(22). Likewise, obesity has been described as another relevant factor (21).…”
Section: Discussionsupporting
confidence: 88%
“…None of them were vaccinated against SARS-CoV-2 at the time of their admission; slightly less than half presented ARDS, and practically all of them were treated with corticosteroids. The worst quality of life outcomes were obtained in the domains of general health, vitality, and mental state, with similar results to those observed by Koullias et al (11), who administered a simpler version of the SF-36 at 6 months after admission for coronavirus disease 2019 (COVID-19). Our results are also consistent with theirs in terms of the acceptable scores obtained in the domains referring to physical issues.…”
Section: Discussionsupporting
confidence: 85%
“…Health-related quality of life (HrQoL) has been insufficiently investigated in critical COVID-19. The physical and mental component scores of SF-36v2®have shown long-lasting deterioration in hospitalised COVID-19, particularly in women and in those aged 41–60 years [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%